2023
DOI: 10.1021/acs.jafc.3c05328
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Mutation of a Non-catalytic Gating Residue Increases the Rate of Pseudomonas aeruginosa d-Arginine Dehydrogenase Catalytic Turnover

Joanna Afokai Quaye,
Daniel Ouedraogo,
Giovanni Gadda

Abstract: Commercial food and l-amino acid industries rely on bioengineered d-amino acid oxidizing enzymes to detect and remove d-amino acid contaminants. However, the bioengineering of enzymes to generate faster biological catalysts has proven difficult as a result of the failure to target specific kinetic steps that limit enzyme turnover, k cat, and the poor understanding of loop dynamics critical for catalysis. Pseudomonas aeruginosa d-arginine dehydrogenase (PaDADH) oxidizes most d-amino acids and is a good candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 74 publications
2
7
0
Order By: Relevance
“…By comparison, this feature is not observed with the Pa DADH wildtype enzyme under both aerobic and anaerobic conditions ( 42 , 44 , 66 , 67 , 69 , 76 , 77 ). In the same way, the flavin semiquinone species was not observed with the E 246 L variant enzyme under anaerobic conditions, although similar kinetic parameters as reported for the aerobic flavin reduction in this study were observed: k red = ∼50 s −1 and K d = 12 mM ( Table 1 ) ( 70 ). The data are consistent with the Pa DADH E 246 L variant reacting with O 2 to yield the flavin semiquinone after flavin reduction and product release, as evidenced by the observed transient increase in the λ 466 nm absorbance of the reduced flavin at 8 s ( Fig.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…By comparison, this feature is not observed with the Pa DADH wildtype enzyme under both aerobic and anaerobic conditions ( 42 , 44 , 66 , 67 , 69 , 76 , 77 ). In the same way, the flavin semiquinone species was not observed with the E 246 L variant enzyme under anaerobic conditions, although similar kinetic parameters as reported for the aerobic flavin reduction in this study were observed: k red = ∼50 s −1 and K d = 12 mM ( Table 1 ) ( 70 ). The data are consistent with the Pa DADH E 246 L variant reacting with O 2 to yield the flavin semiquinone after flavin reduction and product release, as evidenced by the observed transient increase in the λ 466 nm absorbance of the reduced flavin at 8 s ( Fig.…”
Section: Discussionsupporting
confidence: 85%
“…The steady-state kinetic studies of the Pa DADH E246L variant enzyme reported in a previous study yielded a k cat value of 265 ± 5 s −1 , a k cat / K m value of 871,000 ± 35,000 M −1 s −1 , and a K m value of 0.30 ± 0.02 mM with D-arginine ( 70 ). Hence, to determine the effect of the enzyme-generated O 2 • ˉ on Pa DADH E 246 L turnover with D-arginine, assays of the variant enzyme with O 2 as electron acceptor and 0.5 mM D-arginine as substrate were carried out under steady-state conditions.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations